2006
DOI: 10.1126/science.1123497
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for a Functional Second Thymus in Mice

Abstract: The thymus organ supports the development of T cells and is located in the thorax. Here, we report the existence of a second thymus in the mouse neck, which develops after birth and grows to the size of a small lymph node. The cervical thymus had a typical medulla-cortex structure, was found to support T cell development, and could correct T cell deficiency in athymic nude mice upon transplantation. The identification of a regular second thymus in the mouse may provide evolutionary links to thymus organogenesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
111
1
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 140 publications
(122 citation statements)
references
References 19 publications
9
111
1
1
Order By: Relevance
“…It is possible that during its descent, the rudiment may leave behind fragments in some strains, leading to the cervical thymi described before, an extreme manifestation of which are the mutants we present here (37,38). However, in mice deficient for ephrin-B2 expression on NCCs, two contralateral thymic structures were present, along with lymph nodes.…”
Section: Discussionmentioning
confidence: 57%
“…It is possible that during its descent, the rudiment may leave behind fragments in some strains, leading to the cervical thymi described before, an extreme manifestation of which are the mutants we present here (37,38). However, in mice deficient for ephrin-B2 expression on NCCs, two contralateral thymic structures were present, along with lymph nodes.…”
Section: Discussionmentioning
confidence: 57%
“…Using thymectomy procedures, we were unable to identify a role for p21 in T cell survival (30,35). However, such experiments are limited because recent reports have indicated the presence of more than one functional thymus in mice (47). Transfer of the various YF series of mice into appropriate MHC-deficient hosts that express or lack the selecting allele could be another way in which to address this question.…”
Section: Discussionmentioning
confidence: 97%
“…We therefore examined this strain of mice using RANKL and M-CSF-derived osteoclasts, which behaved in a manner similar to the Balb/c-derived cells reported here (data not shown). Different mouse vendors could also be contributing to differences, a possibility that is strengthened by the observation of variability in mouse colonies between vendors [46]. The approach to assess apoptosis also differed in that Hughes et al observed that apoptotic osteoclasts lifted off of the culture surface and chromatin condensation of floating cells was used as the apoptosis marker.…”
Section: Discussionmentioning
confidence: 99%